Altered immediate behavioral response to partial social exclusion: A cross-diagnostic study in patients with borderline personality disorder and persistent depressive disorder - Barton, Barbara; Goerigk, Stephan; Wüstenberg, Torsten; Dewald-Kaufmann, Julia; Reinhard, Matthias A.; Musil, Richard; Ehring, Thomas; Jobst, Andrea; Padberg, Frank (Journal of psychiatric research, 2021)
Borderline personality disorder (BPD) and persistent depressive disorder (PDD) are related to interpersonal dysfunction which might become particularly apparent in situations of social exclusion (SE). While emotional responses to SE have been widely explored, behavioral data in clinical samples are lacking. In this cross-diagnostic study, we applied a variant of the Cyberball paradigm to investigate the dynamic behavioral response to partial SE in BPD and PDD. BPD patients (n = 36), PDD patients (n = 34) and age and gender matched healthy controls (HC) (total n = 70) played experimental (i.e. partial SE Cyberball) and control (i.e. inclusion only) conditions in randomized order. While all groups tended to increase ball tosses towards the excluder in response to SE, this behavioral turn was significantly lower in PDD (p = .03, d = -.30) and trendwise in BPD patients (p = .06, d = -.28). Thus, an altered immediate response to partial SE was observed in BPD and PDD, in addition to the emotional reactions. This study supports the hypothesis of a behavioral coping with SE in BPD and PDD that might be problematic in the long run and provides an experimental paradigm for future research on interpersonal dysfunction.
Gesehen am 07.12.2021